INFLUENCE OF VALUES, BRAND ACTIVISM, BRAND CONSCIOUSNESS, AND BEHAVIORAL INTENTIONS IN PREDICTING NIKE’S SPORTSWEAR CONSUMPTION IN INDONESIA - Ivana Valerie; Evo Sampetua Hariandja (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The goal of this study is to look at the connection between two separate but related types of value orientation, namely terminal and instrumental values, brand activism, brand consciousness, and behavioral intentions. This research confirms a conceptual model for Nike brand sportswear consumption in a growing market, namely Indonesia. This study uses quantitative research techniques with data collection using a Google Forms questionnaire. This study was conducted in Indonesia, with respondents mainly drawn from big cities. Smart-PLS 3.2.9 evaluates the data using the outer and inner models. The validity and reliability tests are part of the outer model, while the goodness of fit test, common method bias, R-square, predictive relevance, T-statistics, and P-value are in the inner model. Within the theoretical framework of this research, the structural equation model is also used to test the linkage of the constructs. The findings illustrate that value (instrumental & terminal) and brand activism, all three affect brand consciousness and consequently, brand consciousness also has an impact on behavioral intention to consume Nike sportswear. Brand activism has a more significant influence on brand consciousness and behavioral intentions than terminal values and instrumental values. Instrumental values have a more significant influence on brand consciousness and behavioral intentions than terminal values. Brand consciousness mediates the relationship between brand activism/instrumental value/terminal value and behavioral intention. This research contributes to international marketing management strategies in emerging markets and increasing consumption of sportswear by increasing brand consciousness through terminal and instrumental value and brand activism. This research aims to uncover the link between value orientation, such as instrumental and terminal values, and brand activism, as well as the underlying effect on brand consciousness and behavioral intention in Nike sportswear. Rokeach (1975) proposed that the two-dimensional value dichotomy was applied to analyze sportswear consumption in a growing market better, specifically Indonesia.